A NOTE ON A KERANGAS (HEATH) FOREST AT SEBULU, EAST KALIMANTAN*) - KUSWATA KARTAWINATA (Reinwardtia, 1980)
Kerangas (heath) forest, that forms islands within the lowland dipterocarp forest, occurred at Sebulu, East Kalimantan. Part of the two of the islands and the transition area between them were investigated. Phytosociologically three communities could be identified, i.e. the Cratoxylum glaucum-Dactylocladus stenostachys, Eugenia palembanica-Ilex hypoglauca, and Shorea ovalis-Eugenia acuminatissima communities. They occurred on sandstone flat, sandstone slope and swampy depression respectively. Only Cratoxylum glaucum-Dactylocladus stenostachys community can be considered kerangas forest proper, whereas the Eugenia palembanica-Ilex hypoglauca community the transition and the Shorea ovalis-Eugenia acuminatissima community a variant of the lowland dipterocarp forest. The soils under these communities were peaty, very acid and low in nutrient contents. The economic value of kerangas forest in terms of timber is very low, hence, it would be better to preserve all kerangas forest as conservation areas and utilize them for research, educational and recreational purposes.